Między wiedzą a widzeniem. O sposobach przedstawiania świata w "Balzakianach" Jacka Dehnela - Kwaśnik, Monika (Załącznik Kulturoznawczy, 2023)
Jacek Dehnel shows in Balzakiana his interest in tradition of realistic prose with a distinctive method of narration and an area of interests. The article shows the constant tension between the methods of depicting the world based on knowledge and an imitation of perceptual processes. This idea is characteristic of the newest prose composition. The article examines the multiple connections of the narration of Balzakiana to plastic arts and the language of the film. Jacek Dehnel’s Balzakiana reminds people about problems which haven’t changed despite the passage of years. Those problems are expressed by means referring to the visuality of any modern artistic media.